2014
DOI: 10.1177/0305735614534004
|View full text |Cite
|
Sign up to set email alerts
|

Perception of melodic intonation in performances with and without vibrato

Abstract: We compared perception of mistuned intervals in unaccompanied melodies performed by trumpet, violin, and voice, and examined whether there were differences between the three timbres in performances with and without vibrato. Participants were 144 university music students. Listeners heard the three unaccompanied solo performers in two vibrato conditions (with and without vibrato), and three intonation conditions (selected melodic intervals were in tune, sharp 25 cents, or flat 25 cents relative to equal tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Some researchers found that listeners' tolerance for tuning deviations differed on the basis of the timbre (i.e., violin, trumpet, or voice) of a stimulus. In those studies, Geringer and colleagues (Geringer, MacLeod, Madsen, et al, 2015;Geringer, MacLeod, & Sasanfar, 2015) speculated that these different standards for pitch performance across instrumental timbres could be related to various acoustical factors of the instruments themselves, top-down cognitive processing factors, and differences in audio presentations (e.g., harmonic/vertical listening vs. melodic/ horizontal listening). Similarly, Ely (1992) indicated that timbre affected participants' judgments of tone pairs even though timbre did not influence their tuning accuracy on a performance task.…”
Section: Pitch-timbre Interactionsmentioning
confidence: 99%
“…Some researchers found that listeners' tolerance for tuning deviations differed on the basis of the timbre (i.e., violin, trumpet, or voice) of a stimulus. In those studies, Geringer and colleagues (Geringer, MacLeod, Madsen, et al, 2015;Geringer, MacLeod, & Sasanfar, 2015) speculated that these different standards for pitch performance across instrumental timbres could be related to various acoustical factors of the instruments themselves, top-down cognitive processing factors, and differences in audio presentations (e.g., harmonic/vertical listening vs. melodic/ horizontal listening). Similarly, Ely (1992) indicated that timbre affected participants' judgments of tone pairs even though timbre did not influence their tuning accuracy on a performance task.…”
Section: Pitch-timbre Interactionsmentioning
confidence: 99%
“…Like language, the building blocks of music (such as intervals, melodies, and cadences) are categorical units which maintain their musical identity across local and global variations, such as different instruments, registers, or keys. Sources of stimulus variability in music include global factors like instrument range and timbre, which can affect pitch judgments (Byo, Schlegel, & Clark, 2011; Geringer, MacLeod, Madsen, & Napoles, 2015; Wapnick & Freeman, 1980). Timbre varies within instruments, as well, depending on the intentions and skill of the performer and performance factors such as the presence of vibrato (Geringer, MacLeod, & Ellis, 2014; Geringer, MacLeod, & Sasanfar, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sources of stimulus variability in music include global factors like instrument range and timbre, which can affect pitch judgments (Byo, Schlegel, & Clark, 2011; Geringer, MacLeod, Madsen, & Napoles, 2015; Wapnick & Freeman, 1980). Timbre varies within instruments, as well, depending on the intentions and skill of the performer and performance factors such as the presence of vibrato (Geringer, MacLeod, & Ellis, 2014; Geringer, MacLeod, & Sasanfar, 2015). Even the emotional state of the performer can affect tempo, dynamics, rhythm, and attack slope (Van Zijl, Toiviainen, Lartillot, & Luck, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…String players must adjust certain notes depending on the key, to maintain correct intonation; for example, they raise the leading tone higher when it is functioning as a different scale degree. There has also been evidence that listeners are more critical of string intonation than with other instruments (Geringer, MacLeod, Madsen, & Napoles, 2015;Geringer, MacLeod, & Sasanfar, 2015). For these reasons, ear training is important at all stages of string instrument learning.…”
mentioning
confidence: 99%